Use of flow modeling to assess sustainability of groundwater resources in the North China Plain. Issue 1 (13th January 2013) - Cao, Guoliang; Zheng, Chunmiao; Scanlon, Bridget R.; Liu, Jie; Li, Wenpeng
Key Points: Regional groundwater model for North China Plain integrating most available data Most comprehensive analyses to date of groundwater storage depletion in the NCP Groundwater sustainability under complex hydrologic and socioeconomic conditions Abstract : [1] The North China Plain (NCP) is one of the global hotspots of groundwater depletion. Currently, our understanding is limited on spatiotemporal variability in depletion and approaches toward more sustainable groundwater development in this region. This study was intended to simulate spatiotemporal variability in groundwater depletion across the entire NCP and explore approaches to reduce future depletion. Simulated predevelopment groundwater recharge (∼13 km 3 /yr) primarily discharged as base flow to rivers and evapotranspiration. Initial groundwater storage was estimated to be 1500 km 3 of drainable storage in shallow aquifers and 40 km 3 of compressive storage in deep aquifers. Simulated groundwater depletion from 1960s to 2008 averaged ∼4 km 3 /yr. Cumulative depletion was 50 km 3 (∼20% of pumpage) in the piedmont district, 103 km 3 (∼20%) in the central plain, and 5 km 3 (12%) in the coastal plain. However, depletion varied with time: ∼2.5 km 3 /yr in the 1970s, ∼4.0 in the 1980s, ∼2.0 in 1990–1996; ∼7.0 in 1997–2001, and ∼4.0 in 2002–2008. Recharge also varied spatially, averaging ∼120 mm/yr and concentrated in the piedmont district (200–350 mm/yr) while lower in the central and coastal plains (50–100 mm/yr). Simulation of several alternatives, including managed aquifer recharge, increased water use efficiency, brackish water use, and interbasin water transfer, indicated that the combination of these strategies could be used to recover groundwater storage by 50 km 3 over a 15‐year period. This study provides valuable insights for developing more sustainable groundwater management options for the NCP; the methods are useful for managing other depleted aquifers.